(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Software like the Hospital administration System improves hospital data administration and accessibility. This C programming language system streamlines hospital administrative procedures by offering patient management, doctor scheduling, and appointment booking. Manual hospital record-keeping causes inefficiencies, data discrepancies, and inaccuracies. This reliable and efficient solution lets healthcare workers access and handle data quickly and correctly. This project aims to construct a user-friendly, modular system that automates appointment scheduling and manages patient records and doctor availability. The system efficiently stores and retrieves patient data, allowing users to add, amend, and delete records. Features to input specialized and scheduling details help match appointment bookings with doctor availability. The Hospital Management System eliminates manual work, data duplication, and scheduling problems by integrating these parts. Modularity makes the patient, doctor, and appointment module versatile and easy to manage because each component runs separately. This project enhances manual data administration by increasing accuracy, decreasing redundancy, and streamlining hospital operations. Due of its versatility, the system can be upgraded to include billing or inventory management to meet hospital needs. The system provides a solid platform for ongoing growth and supports healthcare goals of improved patient care and operational efficiency.